Safaty analysis methods of the structure constructions and buildings based on the theory of risk assessmant - Верюжський, Ю.В. (Proceedings of National Aviation University (archive), 2004)
An efficiency of applying a methodology is considered to be a subject to multi-factor safety analysis of extreme objects problems solution. The key point of the research is a prognosis of behaviour of the structure being degradeated under extremely combined influences. A vastpurposed technique is developed for deterministic and probabilistic numerical modeling, risk assessment, experimental and desighn works of the building extreme objects.